PERILAKU PETANI PADA TAHAPAN PEMETIKAN DALAM PENANGANAN PANEN CENGKEH DI DESA WAODE BURI KECAMATAN KULISUSU UTARA KABUPATEN BUTON UTARA - Harsia Harsia; Salahuddin Salahuddin; Mardin Mardin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
Waode Buri Village is one of the clove production centers in North Buton Regency, but the productivity and quality of the harvest are still below the national average and have decreased every year. This study aims to examine the behavior of farmers at the picking stage in handling clove harvests in Waode Buri Village, North Kulisusu District, North Buton Regency, which includes knowledge, attitudes, and skills. The number of informants in this study was 7 people who were selected based on criteria that have been made by the researcher. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation of local clove farmers. Data were analyzed using the interactive model of Milles and Huberman. The results of the study indicate that the behavior of farmers at the picking stage in handling the harvest is still largely carried out in a hereditary manner, with manual harvesting techniques and at the picking stage, farmers do not use banggul as it should be in the picking process used in other clove producing areas., limited use of tools, and lack of quality control of the harvest. Improving farmers' knowledge and skills through training and extension, as well as government support in providing facilities and market access, is essential to improve the quality and selling value of cloves.